'A Bed of Procrustes': The Aden Protectorate and the Forward Policy 1934–44. Issue 1 (2nd January 2016) - Tripodi, Christian
ABSTRACT: This article explores attempts by British colonial officials based in Aden to extend systems of political administration to the colony's tribal hinterland during the late interwar and early wartime period. Commencing initially with delicate attempts to recast faltering relations between tribal chiefs and their subjects, the policy would culminate a decade later with the despatch of British military units throughout the furthest extents of the protectorate in support of a range of direct political agreements with local rulers that would eventually set the conditions for federation. The intervening years featured a series of little-known debates among various officials on how precisely to cement British influence in the tribal areas, and the philosophy of administration to be pursued to that end. These would expose an element of confusion as to which techniques would best satisfy British policy, and reveal a preference on the part of some for the application of methods atypical of those used elsewhere under Colonial Office jurisdiction, and which drew their inspiration instead from systems of control used on India's volatile frontiers.